Plasma homocysteine, methylene tetrahydrofolate reductase C677T and factor II G20210A polymorphisms, factor VIII, and VWF in central retinal vein occlusion. Issue 11 (1st November 2001) - Boyd, S; Owens, D; Gin, T; Bunce, K; Sherafat, H; Perry, D; Hykin, P G
Abstract : AIMS: To determine whether plasma homocysteine, methylene tetrahydrofolate reductase (MTHFR) C677T and factor II G20210A polymorphisms, factor VIII, and vWF are risk factors for central retinal vein occlusion (CRVO). METHOD: Prospective comparison of 63 consecutive patients with central retinal vein occlusion and 63 age matched controls. Plasma homocysteine and vWF were estimated by ELISA, the MTFHR and factor II G20210A polymorphisms determined by polymerase chain reaction with restriction enzyme product digestion and factor VIII by one stage automated clotting assay. RESULTS: Plasma homocysteine (patients: median 12.4 μmol/l, controls: median 11.6 μmol OR = 1.05, p=0.20), factor VIII (patients: median = 115 U/dl, controls: median = 113 U/dl), and vWF (patients: median = 115 U/dl, controls: median = 108 U/dl) were not statistically higher in patients than in controls. Five CRVO patients and seven controls were homozygous for the MTHFR C677T mutation. One control was heterozygous for the factor II G20210A mutation. CONCLUSION: This study has not identified new risk factors for CRVO.